2008
DOI: 10.1158/0008-5472.can-07-2978
|View full text |Cite
|
Sign up to set email alerts
|

Acetyl-Keto-β-Boswellic Acid Induces Apoptosis through a Death Receptor 5–Mediated Pathway in Prostate Cancer Cells

Abstract: Acetyl-keto-B-boswellic acid (AKBA), a triterpenoid isolated from Boswellia carterri Birdw and Boswellia serrata, has been found to inhibit tumor cell growth and to induce apoptosis. The apoptotic effects and the mechanisms of action of AKBA were studied in LNCaP and PC-3 human prostate cancer cells. AKBA induced apoptosis in both cell lines at concentrations above 10 Mg/mL. AKBA-induced apoptosis was correlated with the activation of caspase-3 and caspase-8 as well as with poly(ADP)ribose polymerase (PARP) cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
72
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 110 publications
(79 citation statements)
references
References 46 publications
6
72
0
1
Order By: Relevance
“…We found that gossypol induced CHOP and that the gene silencing of CHOP by siRNA blocked the effect of gossypol on the induction of death receptors and on TRAILinduced apoptosis. Our findings are similar to those of other studies that indicated that CHOP binds to the DR5 promoter and up-regulates this receptor expression (29,42,43). Although p53 induction has also been linked to DR5 induction (27), we found that gossypol-induced up-regulation of TRAIL receptor DR5 was independent of p53.…”
Section: Discussionsupporting
confidence: 92%
“…We found that gossypol induced CHOP and that the gene silencing of CHOP by siRNA blocked the effect of gossypol on the induction of death receptors and on TRAILinduced apoptosis. Our findings are similar to those of other studies that indicated that CHOP binds to the DR5 promoter and up-regulates this receptor expression (29,42,43). Although p53 induction has also been linked to DR5 induction (27), we found that gossypol-induced up-regulation of TRAIL receptor DR5 was independent of p53.…”
Section: Discussionsupporting
confidence: 92%
“…4D). Consistent with our findings, MG132 (proteasome inhibitor) and triterpenoid also induced DR5 up-regulation through CHOP protein [40,41].…”
Section: Discussionsupporting
confidence: 92%
“…Furthermore, we found a strong upregulation of the bZIP transcription factor DDIT3 -notably independent of p53 -after PDT. Since DDIT3 had been implicated in anti-proliferative effects and the induction of apoptosis by certain anticancer agents, including in PC-3 cells [58], the observed high levels may have also contributed to growth arrest and apoptotic signaling in our experiment after PDT.…”
Section: Discussionmentioning
confidence: 85%